Exponential uptake of HPV self-collected cervical screening testing 2 years since universal availability in Victoria, Australia - Alvin Lee; David Hawkes; Daniel Sweeney; Kerryann Wyatt; Claire Nightingale; Corey Chalmers; Marion Saville (BMC Medicine)
Abstract Background Australia is working towards eliminating cervical cancer as a public health issue by 2035, by achieving an incidence rate of less than 4 cases per 100,000 people. Increasing cervical screening participation, particularly in under-screened groups, is critical to achieving this goal equitably. On 1 December 2017, the National Cervical Screening Program (NCSP) transitioned from two-yearly Papanicolaou smear-based screening to five-yearly primary human papillomavirus (HPV) based cervical screening tests (CST) for all women and people with a cervix aged 25–74 years. Since July 2022, all eligible participants can choose to undertake self-collected CST, a collection method to help overcome barriers to screening. We aimed to investigate self-collection uptake in Victoria, including HPV positivity rates and time to colposcopy, after universal availability. Methods We investigated self-collection uptake by age group, regionality, and screening status as a proportion of all CST from 1 December 2017 until 30 June 2024. We also compared rates of HPV detection, invalid results, and time to colposcopy with practitioner-collected samples during the same period. The analysis presented was conducted using the March 2025 Victorian raw data extract sourced from the National Cancer Screening Register and publicly available screening coverage rates in Victoria. R was used to prepare our descriptive analysis. Results Twenty-nine percent of the 598,055 CST from 1 July 2022 to 30 June 2024 were self-collected compared with 0.41% of 1,279,416 tests prior to universal availability. The findings indicate a notable increase in self-collection uptake in older age groups, regional areas, and under- and never-screened women. While uptake of self-collection increased, there was a reduction in overall screening coverage in 2023. The median time to colposcopy assessment was similar for women who used self-collection and practitioner-collected screening. HPV positivity and invalid rates were low for both collection methods, although there were slightly higher overall positivity and invalid rates in self-collected tests. Conclusions Self-collection was used by a wide range of NCSP participants when universally available, despite a reduction in overall screening coverage. Our findings offer insights for programs seeking to widen population level availability of self-collection for cervical screening.